Estimation of Feed Costs and Feed Efficiency in Typical Dairy Farms of Bangladesh during Coronavirus (Covid-19) Emergency: Implications Toward Feed Support Policy - uddin, Mohammad Mohi (Indian Journal of Dairy Science, 2023)
Feed cost is the highest cost item to the total costs of dairy farming all over the world including India, Pakistan and Bangladesh. Reducing feed costs and increasing feed efficiency-are two promising ways to decrease the cost of milk production and increase the competitiveness nationally and internationally. Feed price in Bangladesh dairy farm is 51% higher than global feed price which has increased further due to the sudden infection of Coronavirus (Covid-19). Therefore, the objective of this paper is to estimate the impact of pandemic novel Coronavirus (COVID-19) prevalence on feed costs and feed efficiency in order to find a suitable feed supporting policy to the dairy farmers. The International Farm Comparison Network (IFCN) Feed Simulation Approach and Technology Impact Policy Impact Calculations (TIPICAL) model was used for estimating feed costs and feed efficiency of the dairy farm with and without Corona situation. The Integrated Dairy Research Network (IDRN) dairy sector and dairy farm database (January 2019 to March 2020) was used where 2019 is considered as without Corona (WOC) and March 2020 is considered as with Corona (WC). Two typical farms: 2 cow farm (BD-2) which is representative of 42% household farm and fourteen cow (BD-14) which is representative of 48% family farms in Bangladesh were selected. The share of feed cost to the total costs of milk production is increased by 9.5% and 8.9% for BD-2/19-WC and BD-14/20-WC, respectively. The purchased feed costs before corona was 22.1 USD/100 kg milk for BD-2/19-WOC and 32.2 USD/100 kg milk for BD-14/19-WOC which is increased to 23.8 USD/100 kg and 35.0 USD/100 kg for BD-2/20-WC and BD-14/20-WC, respectively. The purchased feed costs increased by 7.6% and 8.7% for BD-2/20-WC and BD-14/20-WC, respectively while for the homegrown feed, it is increased even higher which is 14.1% and 9.7%, respectively. The results revealed that decreasing milk price and increasing feed price has direct impact on increasing feed costs of 8.6% and decreasing margin over compound feed costs by 4.5% due to Coronavirus. As a result, an increase in feed cost, decrease in the margin over total feed cost and the feed efficiency (total, energy, and protein efficiency) was observed due to coronavirus (Covid-19) infection. The finding of this study revealed that for short-term and medium-term, farmers might need feed incentives either in the form of reduced feed price or liberalized concentrate feed input market. The outcome of this study is expected to be beneficial for policy makers, feed suppliers and farmers.